2020
DOI: 10.1634/theoncologist.2020-0001
|View full text |Cite
|
Sign up to set email alerts
|

Current Status and Factors Influencing Surgical Options for Breast Cancer in China: A Nationwide Cross-Sectional Survey of 110 Hospitals

Abstract: Background. There are limited nationwide data regarding breast cancer surgery in China. The Chinese Anti-Cancer Association's Committee of Breast Cancer Society and the Chinese Society of Breast Surgeons conducted a nationwide survey to examine the use of and barriers associated with surgical options among patients with breast cancer. Methods. Surveys were sent via e-mail to the directors of 110 centers that performed at least 200 breast cancer operations in 2017. The electronic questionnaire contained 183 que… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
45
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(46 citation statements)
references
References 18 publications
(22 reference statements)
1
45
0
Order By: Relevance
“…Based on the results of these trials, the latest NCCN guidelines also recommended that ALND not be performed in patients with 1-2 involved SLNs who were planning to undergo breast-conserving surgery and subsequent radiotherapy [15]. However, in most developing countries, such as China, the BCR is only approximately 20%, compared to 50%-80% in Western countries [6,16,17]. Even in some leading centres in China, the BCR is only 30% [18].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on the results of these trials, the latest NCCN guidelines also recommended that ALND not be performed in patients with 1-2 involved SLNs who were planning to undergo breast-conserving surgery and subsequent radiotherapy [15]. However, in most developing countries, such as China, the BCR is only approximately 20%, compared to 50%-80% in Western countries [6,16,17]. Even in some leading centres in China, the BCR is only 30% [18].…”
Section: Discussionmentioning
confidence: 99%
“…Even in some leading centres in China, the BCR is only 30% [18]. Because of the low BCR in developing countries and the absence of evidence for ALND omission in Eastern populations, most clinicians in developing countries such as China still hold a conservative view and recommend ALND for patients with positive SLNs [16]. In addition, the ALN status remains one of the most important prognostic factors.…”
Section: Discussionmentioning
confidence: 99%
“…Besides, a close margin was defined as tumor within 1 mm of the inked margin ( 6 ). Most surgeons in our country would re-excise a close margin in patients intraoperatively ( 7 ). However, re-excision surgeries after the first surgery are a source of physical burden, financial burden, anxiety, and worse cosmesis for patients ( 8 ).…”
Section: Introductionmentioning
confidence: 99%
“…BCS is sometimes called lumpectomy, quadrantectomy, partial mastectomy, or segmental mastectomy depending on how much tissue is removed. Some selective breast cancer patients with larger tumor to breast ratio can undergo oncoplastic surgery after partial mastectomy, thus avoiding total mastectomy and obtaining better breast appearance [3][4][5]. Relational data have shown that the rate of positive margins in patients undergoing oncoplastic BCS was signi cantly lower than that of traditional BCS, and there were no differences in either overall survival rates or relapse-free survival rates between the two techniques [4].…”
Section: Introductionmentioning
confidence: 99%